2020
DOI: 10.3389/fimmu.2020.01353
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights in Cutaneous Lupus Erythematosus Immunopathogenesis

Abstract: Cutaneous Lupus Erythematosus (CLE) is a clinically diverse group of autoimmune skin diseases with shared histological features of interface dermatitis and autoantibodies deposited at the dermal-epidermal junction. Various genetic and environmental triggers of CLE promote infiltration of T cells, B cells, neutrophils, antigen presenting cells, and NK cells into lesional skin. In this mini-review, we will discuss the clinical features of CLE, insights into CLE immunopathogenesis, and novel treatment approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 183 publications
(182 reference statements)
0
34
0
13
Order By: Relevance
“…Using novel analyses, we found that DLE lesions harbor a unique immunoglobulin signature and an enrichment of skin B cells compared to ACLE or SCLE lesions. Intriguingly, this B cell signature was highest in patients with CLE without concomitant SLE, including within the entire cohort of DLE patients (2). Our results demonstrate that a B cell gene signature in the skin distinguishes DLE from ACLE and SCLE and that increased B cells in the skin of DLE patients is indicative of a lower rate of accompanying systemic disease.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Using novel analyses, we found that DLE lesions harbor a unique immunoglobulin signature and an enrichment of skin B cells compared to ACLE or SCLE lesions. Intriguingly, this B cell signature was highest in patients with CLE without concomitant SLE, including within the entire cohort of DLE patients (2). Our results demonstrate that a B cell gene signature in the skin distinguishes DLE from ACLE and SCLE and that increased B cells in the skin of DLE patients is indicative of a lower rate of accompanying systemic disease.…”
Section: Introductionmentioning
confidence: 55%
“…SLE involves multiple organ systems, including the skin, where the distinct type of inflammation is termed cutaneous lupus erythematosus (CLE). CLE can occur in isolation or as a skin manifestation associated with underlying systemic lupus erythematosus (SLE) (2). CLE is relatively understudied compared to SLE, which contributes to a lack of understanding of disease heterogeneity in CLE pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous lupus erythematosus (CLE) is a spectrum of autoimmune skin diseases encompassing several clinical subtypes, all of which are characterized by interface dermatitis, or inflammation at the dermal-epidermal junction ( 58 ). The most well-known manifestation of CLE is the characteristic erythematous malar rash, which is associated with systemic lupus erythematosus (SLE).…”
Section: Trm In Cutaneous Lupus Erythematosusmentioning
confidence: 99%
“…1 Subtypes of cutaneous lupus erythematosus (CLE) contained acute CLE, subacute CLE, intermittent CLE and chronic CLE, divided based on chronicity, morphology together with the distribution of skin lesions. 2 Among different subtypes of CLE, discoid lupus erythematosus (DLE) is the most common chronic type. 3 Its skin symptoms include erythematosus, atrophic scarring, dyspigmentation, follicular hyperkeratosis and even alopecia.…”
Section: Introductionmentioning
confidence: 99%